Numerical simulation of phase separation in cathode materials of lithium ion batteries. (1st December 2016) - Hofmann, Tobias; Müller, Ralf; Andrä, Heiko; Zausch, Jochen
Abstract: A nonlinear initial boundary value problem for the lithium ion concentration, the electric potential and the electrode-electrolyte interface currents is introduced on the microscale. The model enables the resolution of porous electrode microstructures. Different exchange current densities for Butler–Volmer interface conditions are evaluated. The Cahn–Hilliard equation is used to describe the phase transition from solid-solution diffusion to two-phase dynamics. The resulting phase-field model is then discretized on a regular mesh. A first-order finite-volume scheme with an adaptive time integration method is applied. The parameters and their effects in the non-convex Helmholtz energy are investigated and explained. Furthermore, the numerical convergence of the scheme is examined. In order to illustrate the method, the charging process of several single-particles and a complex structure is numerically simulated.